HUBUNGAN MEDICATION BELIEFS DENGAN KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE II DENGAN BPJS DI WILAYAH PUSKESMAS KECAMATAN JATINEGARA - Yulia Prabhawaty (2023)
Type II diabetes mellitus (T2DM) is a global disease characterized by blood glucose instability. With 537 million cases by 2023 and a keep increases prevalence each year, T2DM has become the 9th deadliest non-communicable disease in the world. Successful T2DM treatment is based on patient medication adherence. One of the two factors of T2DM medication adherence is predisposing factors, such as medication beliefs and cost difficulties, which in Indonesia itself has been given a solution in the form of BPJS as health insurance. Medication beliefs are a critical component in managing T2DM medication adherence to prevent complications and reduce mortality from T2DM. This study aims to determine the relationship between medication beliefs and medication adherence for T2DM patients with BPJS in the Jatinegara District Health Center area. The research was quantitative with a cross-sectional approach conducted on 134 respondents. Results showed that 82 respondents had negative medication beliefs, and 52 respondents had positive medication beliefs. Level of medication adherence shows low level in 105 respondents, moderate in 23 respondents, and high in 6 respondents. Results of analysis using Spearman's correlation test showed a significant relationship (p<0.05), a positive direction of relationship and a moderate relationship (r=0.409) between the two variables.